Design of boundary combined footings of rectangular shape using a new model (2014)
This paper presents the design of boundary combined footings of rectangular shape using a new model to consider real soil pressure acting on the contact surface of the footing; such pressure is presented in terms of an axial load, moment around the “X” axis and moment around the “Y” axis to each column. The classic model considers an axial load and moment around the transverse axis applied in each column, and when the moments in two directions are taken into account, the maximum pressure throughout the contact surface of the footing is considered the same. The main part of this research is that the proposed model considers real soil pressure and the classic model takes into account the maximum pressure and uniform is considered. It is concluded that the proposed model is more suited to the real conditions and is more economical.